lean2/library/algebra/ring.lean
2016-02-29 13:15:48 -08:00

500 lines
17 KiB
Text
Raw Blame History

This file contains ambiguous Unicode characters

This file contains Unicode characters that might be confused with other characters. If you think that this is intentional, you can safely ignore this warning. Use the Escape button to reveal them.

/-
Copyright (c) 2014 Jeremy Avigad. All rights reserved.
Released under Apache 2.0 license as described in the file LICENSE.
Authors: Jeremy Avigad, Leonardo de Moura
Structures with multiplicative and additive components, including semirings, rings, and fields.
The development is modeled after Isabelle's library.
-/
import logic.eq logic.connectives data.unit data.sigma data.prod
import algebra.binary algebra.group
open eq eq.ops
variable {A : Type}
/- auxiliary classes -/
structure distrib [class] (A : Type) extends has_mul A, has_add A :=
(left_distrib : ∀a b c, mul a (add b c) = add (mul a b) (mul a c))
(right_distrib : ∀a b c, mul (add a b) c = add (mul a c) (mul b c))
theorem left_distrib [distrib A] (a b c : A) : a * (b + c) = a * b + a * c :=
!distrib.left_distrib
theorem right_distrib [distrib A] (a b c : A) : (a + b) * c = a * c + b * c :=
!distrib.right_distrib
structure mul_zero_class [class] (A : Type) extends has_mul A, has_zero A :=
(zero_mul : ∀a, mul zero a = zero)
(mul_zero : ∀a, mul a zero = zero)
theorem zero_mul [simp] [mul_zero_class A] (a : A) : 0 * a = 0 := !mul_zero_class.zero_mul
theorem mul_zero [simp] [mul_zero_class A] (a : A) : a * 0 = 0 := !mul_zero_class.mul_zero
structure zero_ne_one_class [class] (A : Type) extends has_zero A, has_one A :=
(zero_ne_one : zero ≠ one)
theorem zero_ne_one [s: zero_ne_one_class A] : 0 ≠ (1:A) := @zero_ne_one_class.zero_ne_one A s
/- semiring -/
structure semiring [class] (A : Type) extends add_comm_monoid A, monoid A, distrib A,
mul_zero_class A
section semiring
variables [s : semiring A] (a b c : A)
include s
theorem one_add_one_eq_two : 1 + 1 = (2:A) :=
by unfold bit0
theorem ne_zero_of_mul_ne_zero_right {a b : A} (H : a * b ≠ 0) : a ≠ 0 :=
suppose a = 0,
have a * b = 0, by rewrite [this, zero_mul],
H this
theorem ne_zero_of_mul_ne_zero_left {a b : A} (H : a * b ≠ 0) : b ≠ 0 :=
suppose b = 0,
have a * b = 0, by rewrite [this, mul_zero],
H this
local attribute right_distrib [simp]
theorem distrib_three_right (a b c d : A) : (a + b + c) * d = a * d + b * d + c * d :=
by simp
end semiring
/- comm semiring -/
structure comm_semiring [class] (A : Type) extends semiring A, comm_monoid A
-- TODO: we could also define a cancelative comm_semiring, i.e. satisfying
-- c ≠ 0 → c * a = c * b → a = b.
section comm_semiring
variables [s : comm_semiring A] (a b c : A)
include s
protected definition algebra.dvd (a b : A) : Prop := ∃c, b = a * c
definition comm_semiring_has_dvd [instance] [priority algebra.prio] : has_dvd A :=
has_dvd.mk algebra.dvd
theorem dvd.intro {a b c : A} (H : a * c = b) : a b :=
exists.intro _ H⁻¹
theorem dvd_of_mul_right_eq {a b c : A} (H : a * c = b) : a b := dvd.intro H
theorem dvd.intro_left {a b c : A} (H : c * a = b) : a b :=
dvd.intro (by rewrite mul.comm at H; exact H)
theorem dvd_of_mul_left_eq {a b c : A} (H : c * a = b) : a b := dvd.intro_left H
theorem exists_eq_mul_right_of_dvd {a b : A} (H : a b) : ∃c, b = a * c := H
theorem dvd.elim {P : Prop} {a b : A} (H₁ : a b) (H₂ : ∀c, b = a * c → P) : P :=
exists.elim H₁ H₂
theorem exists_eq_mul_left_of_dvd {a b : A} (H : a b) : ∃c, b = c * a :=
dvd.elim H (take c, assume H1 : b = a * c, exists.intro c (H1 ⬝ !mul.comm))
theorem dvd.elim_left {P : Prop} {a b : A} (H₁ : a b) (H₂ : ∀c, b = c * a → P) : P :=
exists.elim (exists_eq_mul_left_of_dvd H₁) (take c, assume H₃ : b = c * a, H₂ c H₃)
theorem dvd.refl [simp] : a a :=
dvd.intro !mul_one
theorem dvd.trans {a b c : A} (H₁ : a b) (H₂ : b c) : a c :=
dvd.elim H₁
(take d, assume H₃ : b = a * d,
dvd.elim H₂
(take e, assume H₄ : c = b * e,
dvd.intro
(show a * (d * e) = c, by rewrite [-mul.assoc, -H₃, H₄])))
theorem eq_zero_of_zero_dvd {a : A} (H : 0 a) : a = 0 :=
dvd.elim H (take c, assume H' : a = 0 * c, H' ⬝ !zero_mul)
theorem dvd_zero [simp] : a 0 := dvd.intro !mul_zero
theorem one_dvd [simp] : 1 a := dvd.intro !one_mul
theorem dvd_mul_right [simp] : a a * b := dvd.intro rfl
theorem dvd_mul_left [simp] : a b * a :=
by simp
theorem dvd_mul_of_dvd_left {a b : A} (H : a b) (c : A) : a b * c :=
dvd.elim H
(take d,
suppose b = a * d,
dvd.intro
(show a * (d * c) = b * c, by simp))
theorem dvd_mul_of_dvd_right {a b : A} (H : a b) (c : A) : a c * b :=
!mul.comm ▸ (dvd_mul_of_dvd_left H _)
theorem mul_dvd_mul {a b c d : A} (dvd_ab : a b) (dvd_cd : c d) : a * c b * d :=
dvd.elim dvd_ab
(take e, suppose b = a * e,
dvd.elim dvd_cd
(take f, suppose d = c * f,
dvd.intro
(show a * c * (e * f) = b * d,
by simp)))
theorem dvd_of_mul_right_dvd {a b c : A} (H : a * b c) : a c :=
dvd.elim H (take d, assume Habdc : c = a * b * d, dvd.intro (!mul.assoc⁻¹ ⬝ Habdc⁻¹))
theorem dvd_of_mul_left_dvd {a b c : A} (H : a * b c) : b c :=
dvd_of_mul_right_dvd (mul.comm a b ▸ H)
theorem dvd_add {a b c : A} (Hab : a b) (Hac : a c) : a b + c :=
dvd.elim Hab
(take d, suppose b = a * d,
dvd.elim Hac
(take e, suppose c = a * e,
dvd.intro (show a * (d + e) = b + c,
by rewrite [left_distrib]; substvars)))
end comm_semiring
/- ring -/
structure ring [class] (A : Type) extends add_comm_group A, monoid A, distrib A
theorem ring.mul_zero [simp] [ring A] (a : A) : a * 0 = 0 :=
have a * 0 + 0 = a * 0 + a * 0, from calc
a * 0 + 0 = a * (0 + 0) : by simp
... = a * 0 + a * 0 : by rewrite left_distrib,
show a * 0 = 0, from (add.left_cancel this)⁻¹
theorem ring.zero_mul [simp] [ring A] (a : A) : 0 * a = 0 :=
have 0 * a + 0 = 0 * a + 0 * a, from calc
0 * a + 0 = (0 + 0) * a : by simp
... = 0 * a + 0 * a : by rewrite right_distrib,
show 0 * a = 0, from (add.left_cancel this)⁻¹
definition ring.to_semiring [trans_instance] [s : ring A] : semiring A :=
⦃ semiring, s,
mul_zero := ring.mul_zero,
zero_mul := ring.zero_mul ⦄
section
variables [s : ring A] (a b c d e : A)
include s
theorem neg_mul_eq_neg_mul : -(a * b) = -a * b :=
neg_eq_of_add_eq_zero
begin
rewrite [-right_distrib, add.right_inv, zero_mul]
end
theorem neg_mul_eq_mul_neg : -(a * b) = a * -b :=
neg_eq_of_add_eq_zero
begin
rewrite [-left_distrib, add.right_inv, mul_zero]
end
theorem neg_mul_eq_neg_mul_symm [simp] : - a * b = - (a * b) := eq.symm !neg_mul_eq_neg_mul
theorem mul_neg_eq_neg_mul_symm [simp] : a * - b = - (a * b) := eq.symm !neg_mul_eq_mul_neg
theorem neg_mul_neg : -a * -b = a * b :=
by simp
theorem neg_mul_comm : -a * b = a * -b :=
by simp
theorem neg_eq_neg_one_mul : -a = -1 * a :=
by simp
theorem mul_sub_left_distrib : a * (b - c) = a * b - a * c :=
calc
a * (b - c) = a * b + a * -c : left_distrib
... = a * b - a * c : by simp
theorem mul_sub_right_distrib : (a - b) * c = a * c - b * c :=
calc
(a - b) * c = a * c + -b * c : right_distrib
... = a * c - b * c : by simp
-- TODO: can calc mode be improved to make this easier?
-- TODO: there is also the other direction. It will be easier when we
-- have the simplifier.
theorem mul_add_eq_mul_add_iff_sub_mul_add_eq : a * e + c = b * e + d ↔ (a - b) * e + c = d :=
calc
a * e + c = b * e + d ↔ a * e + c = d + b * e : by rewrite {b*e+_}add.comm
... ↔ a * e + c - b * e = d : iff.symm !sub_eq_iff_eq_add
... ↔ a * e - b * e + c = d : by rewrite sub_add_eq_add_sub
... ↔ (a - b) * e + c = d : by rewrite mul_sub_right_distrib
theorem mul_add_eq_mul_add_of_sub_mul_add_eq : (a - b) * e + c = d → a * e + c = b * e + d :=
iff.mpr !mul_add_eq_mul_add_iff_sub_mul_add_eq
theorem sub_mul_add_eq_of_mul_add_eq_mul_add : a * e + c = b * e + d → (a - b) * e + c = d :=
iff.mp !mul_add_eq_mul_add_iff_sub_mul_add_eq
theorem mul_neg_one_eq_neg : a * (-1) = -a :=
have a + a * -1 = 0, from calc
a + a * -1 = a * 1 + a * -1 : by simp
... = a * (1 + -1) : left_distrib
... = 0 : by simp,
symm (neg_eq_of_add_eq_zero this)
theorem ne_zero_and_ne_zero_of_mul_ne_zero {a b : A} (H : a * b ≠ 0) : a ≠ 0 ∧ b ≠ 0 :=
have a ≠ 0, from
(suppose a = 0,
have a * b = 0, by rewrite [this, zero_mul],
absurd this H),
have b ≠ 0, from
(suppose b = 0,
have a * b = 0, by rewrite [this, mul_zero],
absurd this H),
and.intro `a ≠ 0` `b ≠ 0`
end
structure comm_ring [class] (A : Type) extends ring A, comm_semigroup A
definition comm_ring.to_comm_semiring [trans_instance] [s : comm_ring A] : comm_semiring A :=
⦃ comm_semiring, s,
mul_zero := mul_zero,
zero_mul := zero_mul ⦄
section
variables [s : comm_ring A] (a b c d e : A)
include s
local attribute left_distrib right_distrib [simp]
theorem mul_self_sub_mul_self_eq : a * a - b * b = (a + b) * (a - b) :=
by simp
theorem mul_self_sub_one_eq : a * a - 1 = (a + 1) * (a - 1) :=
by simp
theorem add_mul_self_eq : (a + b) * (a + b) = a*a + 2*a*b + b*b :=
calc (a + b)*(a + b) = a*a + (1+1)*a*b + b*b : by simp
... = a*a + 2*a*b + b*b : by rewrite one_add_one_eq_two
theorem dvd_neg_iff_dvd : (a -b) ↔ (a b) :=
iff.intro
(suppose a -b,
dvd.elim this
(take c, suppose -b = a * c,
dvd.intro
(show a * -c = b,
by rewrite [-neg_mul_eq_mul_neg, -this, neg_neg])))
(suppose a b,
dvd.elim this
(take c, suppose b = a * c,
dvd.intro
(show a * -c = -b,
by rewrite [-neg_mul_eq_mul_neg, -this])))
theorem dvd_neg_of_dvd : (a b) → (a -b) :=
iff.mpr !dvd_neg_iff_dvd
theorem dvd_of_dvd_neg : (a -b) → (a b) :=
iff.mp !dvd_neg_iff_dvd
theorem neg_dvd_iff_dvd : (-a b) ↔ (a b) :=
iff.intro
(suppose -a b,
dvd.elim this
(take c, suppose b = -a * c,
dvd.intro
(show a * -c = b, by rewrite [-neg_mul_comm, this])))
(suppose a b,
dvd.elim this
(take c, suppose b = a * c,
dvd.intro
(show -a * -c = b, by rewrite [neg_mul_neg, this])))
theorem neg_dvd_of_dvd : (a b) → (-a b) :=
iff.mpr !neg_dvd_iff_dvd
theorem dvd_of_neg_dvd : (-a b) → (a b) :=
iff.mp !neg_dvd_iff_dvd
theorem dvd_sub (H₁ : (a b)) (H₂ : (a c)) : (a b - c) :=
dvd_add H₁ (!dvd_neg_of_dvd H₂)
end
/- integral domains -/
structure no_zero_divisors [class] (A : Type) extends has_mul A, has_zero A :=
(eq_zero_or_eq_zero_of_mul_eq_zero : ∀a b, mul a b = zero → a = zero b = zero)
theorem eq_zero_or_eq_zero_of_mul_eq_zero {A : Type} [no_zero_divisors A] {a b : A}
(H : a * b = 0) :
a = 0 b = 0 :=
!no_zero_divisors.eq_zero_or_eq_zero_of_mul_eq_zero H
theorem eq_zero_of_mul_self_eq_zero {A : Type} [no_zero_divisors A] {a : A} (H : a * a = 0) :
a = 0 :=
or.elim (eq_zero_or_eq_zero_of_mul_eq_zero H) (assume H', H') (assume H', H')
structure integral_domain [class] (A : Type) extends comm_ring A, no_zero_divisors A,
zero_ne_one_class A
section
variables [s : integral_domain A] (a b c d e : A)
include s
theorem mul_ne_zero {a b : A} (H1 : a ≠ 0) (H2 : b ≠ 0) : a * b ≠ 0 :=
suppose a * b = 0,
or.elim (eq_zero_or_eq_zero_of_mul_eq_zero this) (assume H3, H1 H3) (assume H4, H2 H4)
theorem eq_of_mul_eq_mul_right {a b c : A} (Ha : a ≠ 0) (H : b * a = c * a) : b = c :=
have b * a - c * a = 0, from iff.mp !eq_iff_sub_eq_zero H,
have (b - c) * a = 0, by rewrite [mul_sub_right_distrib, this],
have b - c = 0, from or_resolve_left (eq_zero_or_eq_zero_of_mul_eq_zero this) Ha,
iff.elim_right !eq_iff_sub_eq_zero this
theorem eq_of_mul_eq_mul_left {a b c : A} (Ha : a ≠ 0) (H : a * b = a * c) : b = c :=
have a * b - a * c = 0, from iff.mp !eq_iff_sub_eq_zero H,
have a * (b - c) = 0, by rewrite [mul_sub_left_distrib, this],
have b - c = 0, from or_resolve_right (eq_zero_or_eq_zero_of_mul_eq_zero this) Ha,
iff.elim_right !eq_iff_sub_eq_zero this
-- TODO: do we want the iff versions?
theorem eq_zero_of_mul_eq_self_right {a b : A} (H₁ : b ≠ 1) (H₂ : a * b = a) : a = 0 :=
have b - 1 ≠ 0, from
suppose b - 1 = 0, H₁ (!zero_add ▸ eq_add_of_sub_eq this),
have a * b - a = 0, by simp,
have a * (b - 1) = 0, by rewrite [mul_sub_left_distrib, mul_one]; apply this,
show a = 0, from or_resolve_left (eq_zero_or_eq_zero_of_mul_eq_zero this) `b - 1 ≠ 0`
theorem eq_zero_of_mul_eq_self_left {a b : A} (H₁ : b ≠ 1) (H₂ : b * a = a) : a = 0 :=
eq_zero_of_mul_eq_self_right H₁ (!mul.comm ▸ H₂)
theorem mul_self_eq_mul_self_iff (a b : A) : a * a = b * b ↔ a = b a = -b :=
iff.intro
(suppose a * a = b * b,
have (a - b) * (a + b) = 0,
by rewrite [mul.comm, -mul_self_sub_mul_self_eq, this, sub_self],
have a - b = 0 a + b = 0, from !eq_zero_or_eq_zero_of_mul_eq_zero this,
or.elim this
(suppose a - b = 0, or.inl (eq_of_sub_eq_zero this))
(suppose a + b = 0, or.inr (eq_neg_of_add_eq_zero this)))
(suppose a = b a = -b, or.elim this
(suppose a = b, by rewrite this)
(suppose a = -b, by rewrite [this, neg_mul_neg]))
theorem mul_self_eq_one_iff (a : A) : a * a = 1 ↔ a = 1 a = -1 :=
have a * a = 1 * 1 ↔ a = 1 a = -1, from mul_self_eq_mul_self_iff a 1,
by rewrite mul_one at this; exact this
-- TODO: c - b * c → c = 0 b = 1 and variants
theorem dvd_of_mul_dvd_mul_left {a b c : A} (Ha : a ≠ 0) (Hdvd : (a * b a * c)) : (b c) :=
dvd.elim Hdvd
(take d,
suppose a * c = a * b * d,
have b * d = c, from eq_of_mul_eq_mul_left Ha (mul.assoc a b d ▸ this⁻¹),
dvd.intro this)
theorem dvd_of_mul_dvd_mul_right {a b c : A} (Ha : a ≠ 0) (Hdvd : (b * a c * a)) : (b c) :=
dvd.elim Hdvd
(take d,
suppose c * a = b * a * d,
have b * d * a = c * a, from by rewrite [mul.right_comm, -this],
have b * d = c, from eq_of_mul_eq_mul_right Ha this,
dvd.intro this)
end
namespace norm_num
local attribute bit0 bit1 add1 [reducible]
local attribute right_distrib left_distrib [simp]
theorem mul_zero [mul_zero_class A] (a : A) : a * zero = zero :=
by simp
theorem zero_mul [mul_zero_class A] (a : A) : zero * a = zero :=
by simp
theorem mul_one [monoid A] (a : A) : a * one = a :=
by simp
theorem mul_bit0 [distrib A] (a b : A) : a * (bit0 b) = bit0 (a * b) :=
by simp
theorem mul_bit0_helper [distrib A] (a b t : A) (H : a * b = t) : a * (bit0 b) = bit0 t :=
by rewrite -H; simp
theorem mul_bit1 [semiring A] (a b : A) : a * (bit1 b) = bit0 (a * b) + a :=
by simp
theorem mul_bit1_helper [semiring A] (a b s t : A) (Hs : a * b = s) (Ht : bit0 s + a = t) :
a * (bit1 b) = t :=
by simp
theorem subst_into_prod [has_mul A] (l r tl tr t : A) (prl : l = tl) (prr : r = tr)
(prt : tl * tr = t) :
l * r = t :=
by simp
theorem mk_cong (op : A → A) (a b : A) (H : a = b) : op a = op b :=
by simp
theorem neg_add_neg_eq_of_add_add_eq_zero [add_comm_group A] (a b c : A) (H : c + a + b = 0) :
-a + -b = c :=
begin
apply add_neg_eq_of_eq_add,
apply neg_eq_of_add_eq_zero,
simp
end
theorem neg_add_neg_helper [add_comm_group A] (a b c : A) (H : a + b = c) : -a + -b = -c :=
begin apply iff.mp !neg_eq_neg_iff_eq, simp end
theorem neg_add_pos_eq_of_eq_add [add_comm_group A] (a b c : A) (H : b = c + a) : -a + b = c :=
begin apply neg_add_eq_of_eq_add, simp end
theorem neg_add_pos_helper1 [add_comm_group A] (a b c : A) (H : b + c = a) : -a + b = -c :=
begin apply neg_add_eq_of_eq_add, apply eq_add_neg_of_add_eq H end
theorem neg_add_pos_helper2 [add_comm_group A] (a b c : A) (H : a + c = b) : -a + b = c :=
begin apply neg_add_eq_of_eq_add, rewrite H end
theorem pos_add_neg_helper [add_comm_group A] (a b c : A) (H : b + a = c) : a + b = c :=
by simp
theorem sub_eq_add_neg_helper [add_comm_group A] (t₁ t₂ e w₁ w₂: A) (H₁ : t₁ = w₁)
(H₂ : t₂ = w₂) (H : w₁ + -w₂ = e) : t₁ - t₂ = e :=
by simp
theorem pos_add_pos_helper [add_comm_group A] (a b c h₁ h₂ : A) (H₁ : a = h₁) (H₂ : b = h₂)
(H : h₁ + h₂ = c) : a + b = c :=
by simp
theorem subst_into_subtr [add_group A] (l r t : A) (prt : l + -r = t) : l - r = t :=
by simp
theorem neg_neg_helper [add_group A] (a b : A) (H : a = -b) : -a = b :=
by simp
theorem neg_mul_neg_helper [ring A] (a b c : A) (H : a * b = c) : (-a) * (-b) = c :=
by simp
theorem neg_mul_pos_helper [ring A] (a b c : A) (H : a * b = c) : (-a) * b = -c :=
by simp
theorem pos_mul_neg_helper [ring A] (a b c : A) (H : a * b = c) : a * (-b) = -c :=
by simp
end norm_num
attribute [simp]
zero_mul mul_zero
at simplifier.unit
attribute [simp]
neg_mul_eq_neg_mul_symm mul_neg_eq_neg_mul_symm
at simplifier.neg
attribute [simp]
left_distrib right_distrib
at simplifier.distrib